The Role of Orange Gene in Carotenoid Accumulation: Manipulating Chromoplasts Toward a Colored Future - Osorio, Claudia E. (Frontiers in Plant Science, 2019)
Carotenoids are isoprenoid pigments synthesized in plants, algae, and photosynthetic bacteria and fungus. Their role is essential in light capture, photoprotection, pollinator attraction and phytohormone production. Furthermore, they can regulate plant development when they are processed as small signaling molecules. Due to their importance for human health, as promoters of the immune system and antioxidant activity, carotenoids have been used in the pharmaceutical, food and nutraceutical industries. Regulation of carotenoid synthesis and accumulation has been extensively studied. Excellent work has been done unraveling the mode of action of phytoene synthase (PSY), a rate-limiting enzyme of carotenoid biosynthesis pathway, in model species and staple crops. Lately, interest has been turned to Orange protein and its interaction with PSY during carotenoid biosynthesis. Discovered as a dominant mutation in Brassica oleracea, Orange protein regulates carotenoid accumulation by post-transcriptionally regulating PSY, promoting the formation of carotenoid-sequestering structures and also preventing carotenoid degradation. Furthermore, Orange protein contributes to homeostasis regulation, improving plant tolerance to abiotic stress. In this mini-review, the focus is made on recent evidence that elucidates Orange protein mode of action and expression in different plant species. Additionally, strategies are proposed to modify Orange gene by utilization of genome editing techniques. A better understanding of carotenoid biosynthesis and accumulation will lead to a positive impact on the development of healthy food for a growing population.